Pharmacogenetics of Obesity Drug Therapy - Guzman, A.K.; Ding, M.; Xie, Y.; Martin, K.A. (Current Molecular Medicine, 2014)
As the prevalence and severity of obesity and its complications have risen significantly in worldwide populations, behavioral interventions alone have been inconsistent in promoting sufficient, sustained weight loss. Consequently, there has been intense interest in the development of anti-obesity medications as treatment strategies. When coupled with structured lifestyle modifications, pharmacotherapy can enhance weight loss. While less efficacious than bariatric surgery, drug therapy may be an alternative to surgery for some obese patients, and is an emerging strategy for weight maintenance. The goal of pharmacogenetics is to help identify patients who will benefit most from drug therapies while minimizing the risk of adverse effects. In this review, we summarize the pharmacogenetic literature on obesity drugs of the past (sibutramine, rimonabant), present (orlistat, lorcaserin, phentermine, topiramate), and future (buprioprion/naltrexone).
Keywords: orlistat